Penerapan Penggunaan Aplikasi Mobile Phone Berbasis Andronid Terkait Profil Silsilah, Dan Pemasaran Sapi Sonok Madura - Badar Said; Moh . Zali; Deny Sulistyowati (Jurnal ABM Mengabdi, 2022)
Sonok cattle are a culture that still exists on the island of Madura, this culture competes for a pair of female cows to walk with a compact step. Sonok cattle breeders are spread over four districts. The problems faced by Sonok cattle breeders in Waru Barat Village are related to genealogies and profiles that have never been documented, this causes detailed information related to pedigrees and profiles to be unclear. In addition, the marketing process is still carried out with limited media so that a lot of information is not conveyed, such as genealogical details and profiles. One of the villages that is a partner and the majority of its residents are sonok cattle breeders is Waru Barat Village, Waru District, Pamekasan Regency. The service method is a survey that takes samples from a certain time from a population and uses basic data interview techniques. After that, a trial was carried out and some analysis of the application of pedigree, profile, and market applications on Sonok cattle activists, it can be seen that sonok cattle culture activists are greatly facilitated by all the features in the application, pedigree and profile data can be seen through the application so that during sales transactions they can be assured. buyer. From the results of the calculation of the System Usability Scale (SUS) questionnaire filled in by the sonok cow culture activists, the average value is 82. The age of the breeder is 51-60 years (40%) with livestock experience 21-30 years (30%) and the number of maintenance is 2 tail (40%) and ST level 2.25-3 (60%). The results of the analysis show a very good assessment of SUS for Sonok cattle breeders